The Role of Gut Microbiota in Chronic Itch-Evoked Novel Object Recognition-Related Cognitive Dysfunction in Mice - Li, Yujuan; Zhang, Wencui; Sun, Tainning; Liu, Baowen; Manyande, Anne; Xu, Weiguo; Xiang, Hong-Bing (Frontiers in Medicine, 2021)
The high incidence of patients with chronic itch highlights the importance of fundamental research. Recent advances in the interface of gut microbiota have shed new light into exploring this phenomenon. However, it is unknown whether gut microbiota plays a role in chronic itch in rodents with or without cognitive dysfunction. In this study, the role of gut microbiota in diphenylcyclopropenone (DCP)-evoked chronic itch was investigated in mice and hierarchical cluster analysis of novel object recognition test (ORT) results were used to classify DCP-evoked itch model in mice with or without cognitive dysfunction (CD)-like phenotype and 16S ribosomal RNA (rRNA) gene sequencing was used to compare gut bacterial composition between CD (Susceptible) and Non-CD phenotypes (Unsusceptible) in chronic itch mice. Results showed that the microbiota composition was significantly altered by DCP-evoked chronic itch and chronic itch induced novel object recognition-related CD. However, abnormal gut microbiota composition induced by chronic itch may not be correlated with novel object recognition-related CD.